In Arabidopsis thaliana Substrate Recognition and Tissue- as Well as Plastid Type-Specific Expression Define the Roles of Distinct Small Subunits of Isopropylmalate Isomerase - Lächler, Kurt; Clauss, Karen; Imhof, Janet; Crocoll, Christoph; Schulz, Alexander; Halkier, Barbara Ann; Binder, Stefan (Frontiers in Plant Science, 2020)
In Arabidopsis thaliana, the heterodimeric isopropylmalate isomerase (IPMI) is composed of a single large (IPMI LSU1) and one of three different small subunits (IPMI SSU1 to 3). The function of IPMI is defined by the small subunits. IPMI SSU1 is required for Leu biosynthesis and has previously also been proposed to be involved in the first cycle of Met chain elongation, the first phase of the synthesis of Met-derived glucosinolates. IPMI SSU2 and IPMI SSU3 participate in the Met chain elongation pathway. Here, we investigate the role of the three IPMI SSUs through the analysis of the role of the substrate recognition region spanning five amino acids on the substrate specificity of IPMI SSU1. Furthermore, we analyze in detail the expression pattern of fluorophore-tagged IPMI SSUs throughout plant development. Our study shows that the substrate recognition region that differs between IPMI SSU1 and the other two IMPI SSUs determines the substrate preference of IPMI. Expression of IPMI SSU1 is spatially separated from the expression of IPMI SSU2 and IPMI SSU3, and IPMI SSU1 is found in small plastids, whereas IMPI SSU2 and SSU3 are found in chloroplasts. Our data show a distinct role for IMPI SSU1 in Leu biosynthesis and for IMPI SSU2 and SSU3 in the Met chain elongation pathway.